Dust Lattice Mode in Complex Plasma - Bhattacharjee, Saurav (Current Research Progress in Physical Science Vol. 3, 2024)
Complex or Dusty Plasma is an emerging branch of soft condensed matter physics. Interaction mechanism among dust grains immersed in plasma environment has been studied theoretically in presence of asymmetric ion flow and dynamical charging of dust grains. The ion flow induced particle-wake interaction in addition to repulsive Yukawa type of interaction found to play a significant role in driving the coulomb coupling strength between charged grains and hence the vibrational mode. The transition in coupling strength is obtained as a characteristic of ion flow speed and grain size. The results show a damping in strength of interaction in presence of dynamical charging of dust. The type of interaction shows a mixed phase of Wake-Yukawa in subsonic regime and highly Yukawa dominating phase in supersonic regime of ion flow. The results are significant for understanding the thermodynamic properties and the phase behavior of colloidal systems and nanocrystals. The study is expected to play a significant role in controlling the phase behavior and diffusion phenomena in complex plasma in absence of magnetic field.